Experimental Investigation of Air-Water CCFL in the Pressurizer Surge Line of AP1000. (1st December 2016) - Yu, Jiangtao; Zhang, Dalin; Shi, Leitai; Wang, Zhiwei; Yan, Shixian; Dong, Bo; Tian, Wenxi; Su, G. H.; Qiu, Suizheng
Abstract: Countercurrent flow limitation (CCFL) may occur under certain flow conditions in the surge line, restricting the draining of water from the pressurizer and thus affecting the coolant inventory and water level in the reactor pressure vessel (RPV). The complexity of the AP1000 pressurizer surge line structure makes predicting CCFL fairly difficult, and there are still not enough CCFL studies on this complex structure. Based on an extensive literature survey, the authors of this paper are particularly aware of the need for improved CCFL models for the pressurizer surge line of AP1000. To investigate the CCFL phenomenon in the surge line assembly fixture of AP1000, a whole-visual test model of the surge line is designed with a scaling ratio of 1:4, and a test loop is established to carry out visualization experiments with air-water countercurrent flow (CCF). The whole-visual test section made of acrylic material is composed of a pressurizer simulator, a surge line tube, a hot leg T-type tube, and an RPV simulator. The air-water CCF experiments are conducted at atmospheric pressure and room temperature with the pressurizer simulator water level varying from 150 to 900 mm. The visual CCF experimental processes and CCFL phenomena are filmed by a high-speed camera and analyzed in detail. The pressure drops at different CCFL locations are measured and evaluated to explore the relationships between the CCFL characteristics and flow patterns in the surge line. The development process of the CCFL is defined as the CCFL region, which can be divided into different regions according of the changes in water mass flow and CCF flow behavior. The CCFL data are analyzed and compared using the air and water superficial velocities to study the effects of hysteresis and water level. Small discrepancies are found between the data of different water levels, reflecting the small but not-negligible influence of the upper tank water level. Empirical models for the CCFL in the surge line assembly fixture are explored preliminarily using Kutateladze-type correlation and Froude-Ohnesorge correlation. Deficiencies still exist in the present semiempirical models, inspiring a more in-depth study on the empirical models for CCFL in the surge line assembly fixture that considers the complex two-phase flow behaviors in the upper tank and near the joint between the upper tank and surge line tube. The present CCFL data are compared broadly and in detail with groups of CCFL data of similar former experiments to demonstrate the applicability of the present air-water CCFL data to the development of a CCFL prediction model for the prototype large-diameter surge line assembly fixture of the AP600/AP1000. We will perform much more experimental and theoretical work to study the detailed mechanism of these special phenomena and to develop a more applicable CCFL model for the geometry and conditions of the prototype large-diameter surge line assembly fixture.